Record of environmental changes in the sediments of the Łykawe Doły karst depression on the Małopolska Upland - Brzozowicz, Dorota (Acta Geographica Lodziensia, 2024)
The paper describes the results of physicochemical analysis and pollen analysis of the Łykawe Doły site located in a drainless depression with karst genesis. The site is located directly adjacent to the western border of the Małopolska Upland, where under a thin layer of Quaternary sediments there are carbonate rocks undergoing karstification. The aim of the work was to reconstruct changes in the plant cover in the immediate vicinity of the depression and the changes taking place in the depression itself. The dating and palynological analysis showed that the depression of covered karst began to fill with biogenic sediments in the Subboreal period, and its development also took place in the Sub-Atlantic period. Throughout the entire time that the depression was filling with sediments, a peatbog existed within it.